ECONOMIC EFFICIENCY OF PUBLIC EXPENDITURE IN PERU, A LONGITUDINAL ANALYSIS OF HEALTH AND EDUCATION INDICATORS 2001-2019 - Romero Cuadros, Italo Brayan (2023)
Public spending should be aimed at improving the level of well-being of the citizens of a given region, meeting efficiency and equity goals. The purpose of this document is to visualize the behavior of indicators for the period 2001-2019 in a general and sectoral manner in education, health, through the Free Disposal Hull methodology applying the time series conglomerate technique. The results generate two types of clusters separating regions that apply good results and another group that obtain adverse results both at the sectoral level for education, health, and globally, due to regions with high performance and comparatively lower public spending. It is concluded that having a greater amount of resources from the public sector does not necessarily mean greater development of said region, other possible factors should be considered, as is the case of regions such as Apurímac, Ayacucho and Huancavelica that have a high presence of public spending, present a relatively low performance compared to the other regions in all the sectors analyzed, indicating that efficiency should be improved by using a smaller amount of tax revenue.